Investigation into the effectiveness of white‐box T‐way testing. Issue 6 (1st December 2019) - Dutta, Arpita; Patel, Anwesha; Mall, Rajib
Abstract : An unduly large number of test cases are required for effective testing of programmes containing complex decision statements. In this context, modified condition/decision coverage (MC/DC) testing has been acknowledged to provide effective testing using a test suite whose size is linear in the number of the clauses present in a predicate. MC/DC testing is well‐accepted and is mandated by several testing standards. T‐way testing is another prominent testing technique that helps to limit the combinatorial explosion of black‐box test cases. Its application to white‐box testing promises to provide effective testing with a comparatively small number of test cases. The authors empirically investigate the effectiveness of MC/DC testing vis‐à‐vis white‐box pairwise, 3‐way and 4‐way testing.